A NOVEL METHOD FOR DETERMINATION OF TRACE AMOUNTSOF OXYCLOZANID IN THE PHARMACEUTICAL (LEVOZAIN) BYMOLECULAR AND FLAME ATOMIC ABSORPTIONSPECTROPHOTOMETRY USING GOLD AS COMPLEXING METAL - Ali, Fattima; Ali, Shaima (Iraqi Journal of Science, 2024)
A simple, rapid and sensitive spectrophotometric methods for determination oftrace amounts of (OXC) as (OXC-Au(III)) complex in octane as solvent forextraction the complex. The green-blue soluble product give maximum absorption at705 nm, Beer’s law is obeyed over the concentration range of (5-35) μg.ml-1 with(molar absorptivity = 1.606×104 L.mol-1.cm-1), (r = 0.9981), (D.L = 0.0864 μg.ml-1),(%RSD = 2.020), with UV-Vis method.When using indirect FAAS a linear range of (2-16) μg.ml-1, (r = 0.9992), (%RSD =2.667), (D.L = 0.0526 μg.ml-1) with (ε = 6.02×105 L.mol-1cm-1).The optimum conditions for colour development are described. The proposedmethods have been successfully applied for determination of (OXC) in bulk drug